Legislation - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2014)
The power to legislate law is with the legislature, the application of the enacted legislation is on the executive and its subjects and the power to interpret the legislation and of ensuring its compliance lies with the courts. The power of Parliament and the State Legislature in Malaysia is limited by the Federal Constitution. The above two legislative bodies cannot make any law they please. The Parliament as a legislative body at the Federal level is vested with the power to amend or repeal the provisions of the Federal Constitution by way of two third majority votes of both houses of Parliament. A bill is a proposed legislation and it does not become law until it is passed by the legislature. This chapter discusses the different types of bills namely, public bills, private bills and hybrid bills and the law making process in the Parliament. Further, the discussion is also focused on the merits and the demerits of the subsidiary legislation and the constitutional duty of the courts to ensure that no excessive delegation has taken place.